Pengaruh Kompensasi dan Kepuasan Kerja Terhadap Turnover Intention PT. Renesola Distribusi Indonesia - Muhammad Yogie Fitriyanto; Hesty Prima Rini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to determine the problem of increasing turnover intention at PT. Renesola Distribution Indonesia. This research tries to analyze and determine how compensation and job satisfaction can be related to the increase of turnover intention of PT Renesola Distribution Indonesia employees. The data used in this research was obtained with purposive sampling method directed from PT. Renesola Distribution Indonesia production division worker class with a total of 50 employees, which the sample selection criteria is the same amount of compensation. The data method used is multiple linear regression using IBM SPSS 27. Data collection was carried out by distributing questionnaires to the company employees. The results of this research show that the variables compensation and job satisfaction simultaneously have a negative effect on the employes turnover intention of PT Renesola Distribution Indonesia. The Compensation variable partially has a significant negative influence on employes turnover intention of PT Renesola Distribution Indonesia The partial job satisfaction variable has a significant negative influence on employes turnover intention of PT Renesola Distribution Indonesia.